1993
DOI: 10.1148/radiology.189.3.8234695
|View full text |Cite
|
Sign up to set email alerts
|

Hyperintense uterine leiomyoma at T2-weighted MR imaging: differentiation with dynamic enhanced MR imaging and clinical implications.

Abstract: Evaluation of signal intensity at T2-weighted imaging and degree of contrast enhancement at dynamic enhanced MR imaging provide useful information on the nature of leiomyomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
3
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(90 citation statements)
references
References 0 publications
5
81
3
1
Order By: Relevance
“…We found that this variation in the treatment efficacy could be partly predicted by fibroid SI as seen on pretreatment T2-weighted MR images: Low fibroid SI was predictive of a good response to MR-guided focused ultrasound surgery. It has previously been established that low or hypointense SI on T2-weighted MR images reflects low cellularity and/or vascularity (18), while high SI represents vascularization, fluid-rich tissues, or degeneration (19). In hyperintense fibroids, it is difficult to obtain adequate temperature elevation with sonication because high perfusion decreases heat accumulation through the vascular cooling effect (20).…”
Section: Discussionmentioning
confidence: 99%
“…We found that this variation in the treatment efficacy could be partly predicted by fibroid SI as seen on pretreatment T2-weighted MR images: Low fibroid SI was predictive of a good response to MR-guided focused ultrasound surgery. It has previously been established that low or hypointense SI on T2-weighted MR images reflects low cellularity and/or vascularity (18), while high SI represents vascularization, fluid-rich tissues, or degeneration (19). In hyperintense fibroids, it is difficult to obtain adequate temperature elevation with sonication because high perfusion decreases heat accumulation through the vascular cooling effect (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding is typically not seen in the menstrual and first part of the cycle. Furthermore, in women at postmenopausal age where such an enhancement pattern is reported as typical, its visualization may be impaired by the low spatial resolution of dynamic contrastenhanced imaging [17,18]. Slice section of 2 mm with enough spatial resolution is only possible in 3D gradient echo sequences, which may be preferable to standard enhanced 2D sequences.…”
Section: Technical Consideration With Agreementmentioning
confidence: 99%
“…The contradicting results of previous studies may be explained by the differences in blood supply among the three Dynamic contrast-enhanced MRI serves as a predictor of HIFU treatment outcome for uterine fibroids with hyperintensity in T2-weighted images (12) observed that degenerated and cellular uterine fibroids manifested as hyperintense under T2-weighted MRI. There was considerable overlap, and dynamic contrast-enhanced MRI was able to reflect the blood flow of uterine fibroids and distinguish between them.…”
Section: Introductionmentioning
confidence: 65%
“…Dynamic contrast-enhanced MRI is performed using a T1-weighted gradient-echo sequence after pump injection of 0.1 mmol/kg gadolinium, and is able to indicate the perfusion and permeability of a tumor and is used to distinguish malignant lesions from benign lesions, in addition to distinguishing degenerative lesions from 'ordinary̓ lesions. According to a number of studies (12,17,18), dynamic contrast-enhanced MRI may be used to distinguish between degenerative fibroids and cellular fibroids, which both manifest as hyperintense under T2-weighted MRI. Cellular fibroids are copiously supplied by vessels and manifest with regular enhancement on dynamic contrast-enhanced MRI scans.…”
Section: Discussionmentioning
confidence: 99%